Induction chemotherapy followed by radiation versus concurrent chemoradiation in supraglottic laryngeal cancer (Bangladesh Medical Journal Khulna, 2025)
Background: Laryngeal cancer is the most prevalent malignancy affecting the upper aero-digestive tract. The management of locally advanced laryngeal cancer has transitioned from an initial strategy involving primary surgical intervention and/or radiotherapy to contemporary multi-modal approaches that encompass definitive concurrent chemoradiation (CCRT). Objective: This study aimed to evaluate the effectiveness of concurrent chemoradiotherapy and induction chemotherapy followed by radiation in supraglottic laryngeal carcinoma. Methods: A Quasi-experimental study was accomplished in the Department of Radiotherapy of Rajshahi Medical College Hospital, Rajshahi, Bangladesh from July 2020 to June 2021. Sixty patients were selected purposively with biopsyproven squamous cell carcinoma of the supraglottic laryngeal region. Total patients were divided into two equal groups non- randomly. Thirty Arm-A group were treated by concurrent chemo-radiotherapy and 30 Arm-B group patients were treated by induction chemotherapy followed by radiation. Data analysis was done by using the SPSS version 25.0 program. Result: In this study, the male to female ratio was 14:1, with a mean age of 55.8±7.7 years in Arm A and 57±6.8 years in Arm B. The overall response rate was higher in Arm A (80%) compared to Arm B (63.3%), but this difference was not statistically significant (p=0.251). While functional organ preservation was achieved in more patients in Arm A (83.3%) than in Arm B (63.3%), this outcome also did not reach statistical significance (p=0.079). Although toxicities were more common in the concurrent chemoradiation (CCRT) group, these differences were not statistically significant, and all toxicities were effectively managed. Conclusion: Induction chemotherapy followed by radiotherapy is equally effective as concurrent chemoradiation for patients with locally advanced supraglottic laryngeal cancer, in terms of local control and preservation of laryngeal function without any added toxicities and may be reasonable approach in low resource set-up.Bang Med J Khulna 2023; 56: 08-13